African swine fever virus ubiquitin-conjugating enzyme pI215L inhibits IFN-I signaling pathway through STAT2 degradation - Elena Riera; Raquel García-Belmonte; Ricardo Madrid; Ricardo Madrid; Daniel Pérez-Núñez; Yolanda Revilla (Frontiers in Microbiology, 2023)
African swine fever virus (ASFV) is the causative agent of one of the most lethal diseases affecting domestic pig and wild boar, which is endangering the swine industry due to its rapid expansion. ASFV has developed different mechanisms to evade the host immune response, including inhibition of type I IFN (IFN-I) production and signaling, since IFN-I is a key element in the cellular antiviral response. Here, we report a novel mechanism of evasion of the IFN-I signaling pathway carried out by the ASFV ubiquitin-conjugating enzyme pI215L. Our data showed that pI215L inhibited IFN-stimulated response element (ISRE) activity and the consecutive mRNA induction of the IFN-stimulated genes ISG15 and IFIT1 through the ubiquitination and proteasomal degradation of STAT2. Additionally, by immunofluorescence, co-immunoprecipitation and nucleus-cytoplasm fractionation approaches, we have confirmed the interaction and colocalization of STAT2 and pI215L, in ectopic experiments and during ASFV infection. Moreover, expression of the catalytic mutant (I215L-C85A) did not inhibit the induction of ISG15 and IFIT1, nor the activity of ISRE. Furthermore, we confirmed that STAT2 degradation by pI215L is dependent on its catalytic activity, since expression of the pI215L-C85A mutant did not affect STAT2 levels, compared to the wild-type protein. Yet, our data reveal that the interaction of pI215L with STAT2 does not require the integrity of its catalytic domain since the pI215L-C85A mutant co-immunoprecipitates with STAT2. All these findings reveal, for the first time, the involvement of E2-ubiquitin-conjugating enzyme activity of pI215L in the immune response modulation.